2020
DOI: 10.1080/02656736.2020.1744741
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of microwave ablation treatment for secondary hyperparathyroidism: systematic review and meta-analysis

Abstract: Purpose: The present systematic review and meta-analysis was designed to evaluate the efficacy and safety of microwave ablation (MWA) treatment for secondary hyperparathyroidism (SHPT). Materials and methods: The study authors systematically searched the Web of Science, Cochrane Library, PubMed, Embase and Ovid databases for studies published in English prior to 7October 2019. All studies included in the meta-analysis measured levels of parathyroid hormone (PTH), calcium and phosphorus, and included data relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 42 publications
0
7
0
2
Order By: Relevance
“…[3][4][5][6][7][8] Microwave ablation, as a minimally invasive therapeutic approach causing parathyroid cells to lose their endocrine functionality, has been increasingly used to treat SHPT. [9][10][11][12][13] Our preliminary study also shows that microwave ablation could be an alternative for secondary hyperparathyroidism in patients with maintenance hemodialysis. The long-term superiority of microwave ablation, however, should be clarified further.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…[3][4][5][6][7][8] Microwave ablation, as a minimally invasive therapeutic approach causing parathyroid cells to lose their endocrine functionality, has been increasingly used to treat SHPT. [9][10][11][12][13] Our preliminary study also shows that microwave ablation could be an alternative for secondary hyperparathyroidism in patients with maintenance hemodialysis. The long-term superiority of microwave ablation, however, should be clarified further.…”
Section: Introductionmentioning
confidence: 58%
“…Recently, a meta-analysis including 233 patients with follow-up duration up to 23 months indicated that microwave ablation may be effective and safe in treating SHPT patients. 11 Another comparative study on microwave ablation vs. parathyroidectomy suggested microwave ablation is an alternative and may be before parathyroidectomy. 14 In addition, microwave ablation may also be effective and safe to manage recurrent and persistent SHPT after parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Our meta-analysis results revealed that PTH, serum calcium and phosphorus levels were significantly reduced at week 1, 1 month, 6 months and end of the follow-up period after MWA of SHPT patients. Different from the results of previous meta-analysis study [51], the current meta-analysis study has fully gathered the data from a wide range of results and provided more indepth insights on important clinical results. Also, due to the inclusion of additional studies and larger amounts of pooling, the results are different from that of the previous metaanalysis.…”
Section: Discussionmentioning
confidence: 99%
“…Also, due to the inclusion of additional studies and larger amounts of pooling, the results are different from that of the previous metaanalysis. A previous meta-analysis conducted by Cao et al [51] has been limited due to inclusion of only eight studies that compared pre-ablative and post-ablative clinical results. The present study included 18 additional eligible studies.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided percutaneous ablation therapy is minimally invasive and reproducible, and has been more widely used to treat hyperparathyroidism. Some previous studies showed that MWA or RFA could indeed reduce PTH levels and is effective for SHPT [10][11][12] , and are not inferior to PTX in safety and e cacy 7,12−15 , but the comparisons of PTX and RFA in hospital stay, economic costs, and especially long-term results are less.…”
mentioning
confidence: 99%